Ultrasonic Elastography of the Rectus Femoris, a Potential Tool to Predict Sarcopenia in Patients With Chronic Obstructive Pulmonary Disease - Deng, Mingming; Zhou, Xiaoming; Li, Yanxia; Yin, Yan; Liang, Chaonan; Zhang, Qin; Lu, Jingwen; Wang, Mengchan; Wang, Yu; Sun, Yue; Li, Ruixia; Yan, Liming; et al. (Frontiers in Physiology, 2022)
Purpose: Skeletal muscle dysfunction is common in patients with chronic obstructive pulmonary disease (COPD) and is associated with a poor prognosis. Abnormal muscle quantity of the lower limbs is a manifestation of skeletal muscle dysfunction in patients with COPD. Shear wave ultrasound elastography (SWE) is a novel and possible tool to evaluate qualitative muscle parameters. This study explores the feasibility of SWE to measure the stiffness of the rectus femoris and evaluates its value in predicting sarcopenia in patients with COPD. Methods: Ultrasound examination of the rectus femoris was performed to determine the mean elasticity index (SWEmean), cross-sectional area (RFcsa), and thickness (RFthick) using grayscale ultrasonography (US) and SWE in 53 patients with COPD and 23 age-matched non-COPD healthy controls. The serum levels of circulating biomarkers (GDF15, resistin, and TNF-α) were measured using ELISA. The definition of sarcopenia followed the guidelines from the Asian Working Group for Sarcopenia. Receiver operating characteristic (ROC) curve analysis of the SWEmean, RFthick, and RFcsa was used to evaluate their predictive ability for sarcopenia. Results: The intraobserver and interobserver repeatability of SWE performance was excellent (all correlation coefficients > 0.95; p < 0.05). The SWEmean of the rectus femoris in patients with COPD (8.98 ± 3.12 kPa) was decreased compared with that in healthy controls (17.00 ± 5.14 kPa) and decreased with advanced global initiative for chronic obstructive lung disease (GOLD) stage. Furthermore, SWEmean was found to be independent of sex, height, and body mass, and a lower SWEmean in patients with COPD was positively associated with reduced pulmonary function, worse physical function, poor exercise tolerance, decreased muscle strength, and worse dyspnea index score. The correlation between physical function [five-repetition sit-to-stand test (5STST)], muscle function, and SWEmean was higher than those of RFthick and RFcsa. In addition, SWEmean was negatively correlated with serum GDF15 levels (r = −0.472, p < 0.001), serum resistin levels (r = −0.291, p = 0.035), and serum TNF-α levels (r = −0.433, p = 0.001). Finally, the predictive power of SWEmean [area under the curve (AUC): 0.863] in the diagnosis of sarcopenia was higher than that of RFthick (AUC: 0.802) and RFcsa (AUC: 0.816). Conclusion: Compared with grayscale US, SWE was not affected by the patient’s height, weight, or BMI and better represented skeletal muscle function and physical function. Furthermore, SWE is a promising potential tool to predict sarcopenia in patients with COPD.